Evaluation of the use of recycled concrete aggregate in structural concrete - Lim, Wee Fong (2011)
In response to the government’s call for sustainable construction, there is a need to divert the construction and demolition (C&D) waste away from the landfills and an urgency to source for alternative materials to replace natural aggregates, which are mainly imported from neighbouring countries. One feasible solution is to produce structural concrete using recycled concrete aggregate (RCA) derived from C&D waste. Due to the fact that the characteristics of RCA are different from those of the natural coarse aggregate (NCA), the use of RCA in structural concrete has always been met with scepticism. This report describes a research study that carried out to investigate the feasibility of using a proposed rational concrete mix design method to overcome the barriers that restrict its use in structural concrete. First of all, laboratory tests were performed to determine the properties of RCA and the results were either used to compare with the corresponding properties of NCA or to check for their conformities with the specifications and standards. Tests were carried out to measure its geometrical, mechanical & physical, thermal & weathering properties and chemical composition. Due to the presence of attached mortar, RCA tends to lose out in the mechanical and physical properties but gain in shape index and surface texture. On the other hand, RCA is stable volumetrically and it can also be considered as an inert material in a concrete mix since it will not react readily with the other concrete components. Concrete mix designs were formulated for the full range of RCA contents (up to 100% replacement level) at different water-to-cement (W/C) ratios. A design slump of 125mm was used as the acceptance criteria for specimen preparation. For the same W/C ratio, the control mix (concrete mix with 0% RCA content) was used as a basis for comparison. The compressive strength test results illustrated that the use of RCA in low- and medium-strength concrete (between W/C ratio 0.67 and 0.35 respectively) has negligible effect on their performance. Conversely, there was an insignificant decrease in compressive strength with the increase in RCA content for high-strength concrete (W/C ratio < 0.45).